Framework para modelos de mensuração de desempenho tecnológico em sistemas de produção agrícola - Vaz, Monica Cristine Scherer (2019)
The improvement of the agricultural productivity is mainly due to the development of researches and innovations that aim to enhancement and development of new technologies. A challenge for the agriculture professionals towards the rural producers is about performing an impartial evaluation non-subjective of the productive potential of a set of rural enterprises. The goal of this thesis is to develop a framework for the creation and measurement of index for the agriculture production process, regarding the differences in potential between small, medium and large producers, as well as the frequent technological changes in the sector. For this purpose there was increased in a studied model and multicriteria of supporting to the decision called Simple Additive Weighting (SAW) was used with a Fuzzy approach, for inferring a degree of importance for each technology, regarding criteria as quality improvement, cost reduction, risks, time for the production and impacts on the environment. With these characters, the framework named AgroIndicator was developed and validated in 9 productive units of grains whose belong to the Reference Network for Familiar Agriculture, in the North region from Paraná state. Through the index measurement the Technologic Capacity that varies from 0 to 1, the average between the units was in 0,75 and were identified the technologies with higher and smaller adhesion by the producers, as well as, the production chain phase where it is found the greatest difficulties of technologies adoption. The analysis of index has created inputs for the preparation of improvement plans that may be effectively executed. The developed framework allows the creation of any model of mensuration in the agriculture area, not only related to the use of technologies, since the structure is within the standards according to the definition and necessity of the professional from the agriculture area.